Strategi Harga dan Kualitas Produk dalam Meningkatkan Kepuasan Konsumen pada Industri Roti - Fujawati, Eli; Susnita, Tia Aprilia; Ratnasari, Neneng (Journal of Innovation in Management, Accounting and Business, 2024)
This research aims to examine the influence of price and product quality on consumer satisfaction at the Fariz Bread Factory in Cihaur Village, Majalengka Regency. Rapid growth in the business industry, especially in the culinary sector, requires companies to innovate in their products to attract consumer interest and ensure their satisfaction. This research uses descriptive and verification methods by collecting data through questionnaires from 94 respondents. The results of the analysis show that price and product quality have a positive and significant effect on consumer satisfaction. The correlation between price and consumer satisfaction is moderate, while the correlation between product quality and consumer satisfaction is strong. Together, price and product quality can explain about 52.20% of the variation in consumer satisfaction. These findings emphasize the importance of maintaining reasonable prices and high product quality to increase consumer satisfaction. Company management is expected to pay attention to consumer preferences and maintain product quality standards and competitive prices to win in a competitive market.